An Improved Protocol for the Aldehyde Olefination Reaction Using (bmim) () as Reaction Medium - Vivek Srivastava (Journal of Chemistry, 2013)
[Ru(COD)Cl2]/CuCl2·2H2O/LiCl catalytic system works efficiently in ionic liquid media for aldehyde olefination reaction. It offers good yield and selectivity with the added advantage of 5 times recyclability for [Ru(COD)Cl2] /CuCl2·2H2O/LiCl catalytic system. We also successfully reduced the reaction time from 12 hours to 9 hours for the aldehyde olefination reaction.